(untitled) (Journal of the College of Education for Women, 2021)
It is no doubt that dialogue is a behavior for human communication. It varies according to the place and occasion that requires it. Dialogues are of two types: positive purposeful and negative non-purposeful. The study aims to shed light on those patterns of dialogues contained in the Quranic stories represented by the characters and events participating in that dialogue activity. To expand the circle of social relations, and in order to make these relationships a success, there are several rules that must be adhered to.For instance, the dialogue should not be tolerant to a personal opinion, or prolonged, or should not deviate from its text. The expression of polite dialogue has been raised in recognition of these dialogue etiquette. To achieve this goal, one needs logical evidence that leads to persuasion, by taking into account the private and public psyche participating in the dialogue event. One further needs to link the ancestors backwards by recognizing the suffering of the prophets while communicating the heavenly messages. As for the approach used in the analysis, it is the mechanism of descriptive narration. It involves narrating the events and characters of the dialogue process using a multiplicity of patterns, such as the self-dialogue, the monologue dialogue, and the supreme dialogue. It can be said that the Quranic text is a vessel that contains a dialogue in all its forms, starting with the Almighty’s dialogue with his angels to His dialogue with Satan as well as His prophets. The study helps to strength the bonds of communication between the interlocutors by accepting the different points of view.